28 Heart Rate is not Related to Survival in Patients with Heart Failure and Atrial Fibrillation. (6th June 2015) - Hawkey, Sean; Levin, Daniel; Mohan, Mohapradeep; Baig, Fatima; Iskandar, Muhammad; Rutherford, Lynn; Lang, Chim; Choy, Anna
Abstract : Introduction: Atrial fibrillation (AF) is common in patients with chronic heart failure (CHF), and is associated with significant morbidity and mortality. Although there is robust evidence that heart rate is a risk factor in CHF and that reducing elevated heart rates improves survival in patients who are in sinus rhythm, the importance of strict heart rate control in AF is still not clear. This study sought to investigate the influence of resting ventricular rate on survival in CHF, comparing those who are in sinus rhythm to those in AF. Methods: A total of 1415 CHF patients (mean age 76+-11 years, 36% females, 65% IHD, 41% NYHA II, 44% NYHA III, 14% NYHA IV), of whom 62% (n = 875) were in sinus rhythm and 38% (n = 540) in permanent AF were evaluated from the BIOSTAT-CHF Scotland study. Patients from both in-patient and out-patient settings were included. We analysed the heart rate and rhythm data recorded on a 12 lead ECG at the baseline review. Multivariate Cox proportional hazards models and Kaplan-Meier curves were used to assess the influence of heart rate on survival in CHF patients with AF or sinus rhythm. Results: During a median per-person follow-up of 1.5 yrs (QIR 0.7–2.2), there were 330 (23%) all-cause deaths. Although Kaplan-Meier survival curves displayed significant differences between the AF and sinus rhythm groups (log-rank test p = 0.014), multivariate Cox survival models showed no significant difference between the 2 groups (hazard ratio [HR]: 0.98, 95% CI: 0.75–1.29; p = 0.9). When assessing the influence of heart rate, multivariate Cox models showed that higher heart rates (per 10 beats/min increments) were associated with worse survival in patients in sinus rhythm (HR: 1.14, 95% CI: 1.03–1.25; p = 0.008), but not for those in AF (HR: 0.98, 95% CI: 0.91–1.07, p = 0.7), for both preserved and reduced ejection fraction heart failure. When separated into two categories (heart rate <80bpm vs. ≥80 bpm), those in sinus rhythm with a heart rate ≥80 bpm had a significantly worse survival than those with a heart rate <80 bpm (HR: 1.57, 95% CI: 1.10–2.23, p = 0.012). Conclusion: Although higher heart rate was associated with worse survival for CHF patients in sinus rhythm, it does not appear to be associated with survival in those who are in AF. These findings question the value of strict heart rate control in CHF patients with atrial fibrillation, thus necessitating further research in this area.